Branding Budaya Lokal Desa Paubokol Melalui Komunikasi Digital di Media Sosial Instagram - R. Hiro Nugroho Rotisno; Meylisa Yuliastuti Sahan; Elisabeth Date Masan Welin (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
This study highlights the role of social media, particularly Instagram, as a digital communication tool to promote and preserve the local culture of Paubokol Village. This village has a unique cultural heritage, but its recognition and appreciation are still limited among people outside the area. By utilizing Instagram as the primary medium, this study focuses on effective digital communication strategies in presenting visual content and cultural narratives. The communication techniques applied include selecting representative images, creating engaging stories, and delivering information interactively to attract a wider audience. The results of this activity indicate that the use of Instagram not only increases public awareness of the cultural values ​​of Paubokol Village but also builds more constructive relationships between local residents and viewers from outside the area. Engaging visual content and informative narratives play a significant role in fostering a higher appreciation of cultural heritage and encouraging support for the preservation and development of the village's potential. This study illustrates how social media can function as a strategic communication tool in promoting local culture, expanding the reach of information, and creating a dynamic space for cultural interaction between the village community and the wider public. These findings open up opportunities for the development of more innovative digital strategies for local cultural preservation.